Sublethal Exposure to Urea Induces Changes in Erythrocyte Morphology in Rhacophorus maximus Tadpoles - Nongkynrih, Susan Jones; Shangpliang, P. Wankitlang; Hooroo, Rupa Nylla K.; Hajong, Sudhanya Ray (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Nitrogen-based fertilizers used in agriculture can impact aquatic organisms when they enter water bodies, affecting the development, behavior, and survival. Haematological studies showed that limited information exists on how nitrogen fertilizers specifically affect the blood of anuran tadpoles. To investigate this, urea (CO(NH2)2), a commonly used fertilizer in Meghalaya, was studied to understand if there is any potential effect on the red blood cell morphology of Rhacophorus maximus tadpoles. The experiment involved exposing laboratory reared tadpoles at Gosner stage 27 to varying sub-lethal doses of urea (1, 5, and 10 g/L) over a 14-day period. Analysis of the red blood cells using light microscopy and scanning electron microscopy revealed some noticeable changes in cell shape, including membrane internalization and membrane disintegration, lobopodial projections, ruptured, oblong, crenulated and contracted cells. Statistical analysis confirmed differences in the percentage of abnormal shaped red blood cells, indicating the potential stress induced by the fertilizer on this anuran species. These findings emphasize the need for conservation efforts to protect the breeding habitats of these organisms against such stressors.